Concentrations and δD values of biomarkers in sediment cores H7 and H11 from Hala Hu, China - Aichner, Bernhard; Callegaro, Alice; van der Meer, Marcel T J; Wünnemann, Bernd; Yan, Dada; Zhang, Yongzhan; Barbante, Carlo; Sachse, Dirk (PANGAEA, 2021)
Hala Hu is located on the northern margin of the Tibetan Plateau (97.24 - 97.47°E, 38.12 - 38.25°N, 4,078 m above sea level), along the modern marginal zone between the Asian Summer Monsoon (ASM) and westerlies influences. Cores H11 and H7 were drilled at the deepest point (65 m) of the lake and extend from 0 - 262 cm (H11) and from 212 to 636 cm (H7) depth, respectively. According to the age-model (Yan et al., 2020) the covered time periods are modern to 9216 cal yr BP and 7462 - 23610 cal yr BP. We analysed the concentrations and hydrogen isotopic compositions of different aquatic (alkenones, mid-chain n-alkenes, C20-HBIs) and terrestrial (long-chain n-alkanes) biomarker groups. Further, monoanhydrous sugars (firemarkers) were analysed in core H11. The principal aim of this study was to evaluate hydroclimate dynamics and ecosystem responses since the last glacial, in a typical glacier influenced, high-altitude and lacustrine ecosystem.
Keywords: Alkenone; Biomarker; China; highly branched isoprenoid (HBI); isotopes; n-alkane; n-alkene; Paleoclimate; Sediment core; Tibetan Plateau